Epilepsy in elderly patients: focus on treatment - Annalisa Amidei; Isabella Righini; Loredana Petrucci; Melania Guida; Alfonso Iudice (Clinical Management Issues, 2012)
Epilepsy is a disorder widely distributed across all age groups, although its incidence and prevalence favours elderly patients. In this population the development of epilepsy is mainlyrelated to other brain disorders that facilitate the occurrence of late seizures, mostly of focal onset. Apart from the difficulties faced in current practice with the appropriate diagnosis of the epileptic nature of the episodes, old subjects require an individualised drug treatment, tailored on their characteristics, such as comorbidity, polytherapy, age-associated biological impairment and compliance. Among the various antiepileptic drugs available for the treatment of epilepsy, rational selection and combination of drugs should drive both initiation and maintenance of the treatment. Choice of antiepileptic drugs should first focus on avoidance of adverse effects and potential drug interactions. The pharmacological control of seizures is usually favourable at this age, with a good prognosis. However, alternative therapeutic options should be considered as soon as drug-response is unsatisfactory.